Impact of Performance Appraisal System on Employee Productivity in Nepal Telecom - Mukhiya, Raj Kumar (Nepalese Journal of Management, 2024)
This study examines the impact of performance appraisal system on employee productivity in the context of Nepal Telecom. Employee productivity is the dependent variable. The independent variables are communication, training and development, rewards and recognition, performance rating and feedback system. The primary source of data is used to assess the opinions of the respondents regarding performance appraisal system and level of productivity in Nepal Telecom. The study is based on primary data of 200 respondents. To achieve the purpose of the study, structured questionnaire is prepared. The correlation coefficients and regression models are estimated to test the significance and importance of performance appraisal system on employee productivity in Nepal Telecom. The study showed that performance rating system has a positive impact on employee productivity. It shows that better performance rating system in an organization leads to increase in employee productivity. In addition, feedback system has a positive impact on employee productivity. It implies that better feedback system in an organization leads to increase in employee productivity. Likewise, communication has a positive impact on employee productivity. It means better communication in an organization leads to increase in employee productivity. Moreover, training and development have positive impact on employee productivity. It implies that increase in training and development in organization leads to increase in employee productivity. The result also revealed that reward and recognition have positive impact on employee productivity. It implies that better reward and recognition in an organization leads to increase in employee productivity.